AKTIVITAS ANTIBAKTERI EKSTRAK DAN FRAKSI DAUN GELINGGANG TERHADAP BAKTERI Propionibacterium - Fildayanti Fildayanti; Herlina Ekapratama; Rika Melati (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Farmasi Riau, 2026)
Gelinggang leaves (Senna alata (L.) Roxb.) have traditionally been used to treat skin diseases such as itching, ringworm, scabies, tinea versicolor, and acne. One of the main bacteria involved in acne pathogenesis is Propionibacterium acnes. Previous studies reported strong antibacterial activity of ethanol extracts of gelinggang leaves; however, comparative data between ethanol extract and its fractions remain limited. This study aimed to evaluate the antibacterial activity of the 96% ethanol extract, n-hexane fraction, and ethyl acetate fraction of gelinggang leaves against Propionibacterium acnes. This experimental laboratory research used the disk diffusion method at concentrations of 5%, 7.5%, 10%, 12.5%, and 15%. Clindamycin 1% served as a positive control, while DMSO was used as a negative control. Phytochemical screening was conducted to identify secondary metabolites. Results showed that the ethanol extract and ethyl acetate fraction contained alkaloids, flavonoids, saponins, and tannins, whereas the n-hexane fraction contained only tannins. The highest antibacterial activity was found in the ethyl acetate fraction with an inhibition zone of 6.65±0.69 mm, followed by the ethanol extract (5.87±0.31 mm) and the n-hexane fraction (3.69±0.47 mm) at 15% concentration. Based on inhibition classification, the ethyl acetate fraction showed moderate antibacterial activity. These findings indicate that the ethyl acetate fraction has potential as a natural antibacterial agent against Propionibacterium acnes due to its ability to extract semi-polar active compounds